A niobium-yttrium co-doped single-crystal ternary positive electrode material, a preparation method and application thereof

CN122918685APending Publication Date: 2026-10-16安徽巡鹰新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611053708.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种铌钇共掺杂的单晶三元正极材料及其制备方法和应用,以解决单晶三元正极材料制备工艺存在的工艺复杂以及结构稳定性差、循环性能差的技术问题

Benefits of technology

本发明在保证正极材料常温电化学性能的前提下,为提高正极材料的高温电化学性能和结构稳定性,本发明采用三段高温烧结法对三元前驱体进行铌和钇共掺杂改性,通过精确控制烧结过程的升温阶段与保温时间,实现了晶粒的均匀生长和掺杂元素的高效固溶。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918685A_ABST
    Figure CN122918685A_ABST
Patent Text Reader

Abstract

The application discloses a niobium-yttrium co-doped single-crystal ternary positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The preparation method comprises the following steps: step one, ball-milling and mixing a ternary precursor, a lithium source, an additive Nb2O5 and Y2O3; step two, under an oxygen atmosphere, three-stage high-temperature sintering is performed on the mixed material; in the first stage, the temperature is raised from room temperature to 450-550 DEG C at a temperature rising rate of 3-5 DEG C / min, and the temperature is kept for 1-2 h; in the second stage, the temperature is raised to 750-850 DEG C at a temperature rising rate of 2-3 DEG C / min, and the temperature is kept for 4-6 h; in the third stage, the temperature is raised to 930-950 DEG C at a temperature rising rate of 2-3 DEG C / min, and the temperature is kept for 10-14 h; and step three, after sintering, the niobium-yttrium co-doped single-crystal ternary positive electrode material is obtained through sieving. Through accurate control of the sintering process, uniform growth of the crystal grains and efficient solid solution of the doped elements are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a niobium-yttrium co-doped single-crystal ternary cathode material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries have been widely used in various fields due to their high energy density, long cycle life, and lack of memory effect. The cathode material, as a key component of lithium-ion batteries, directly affects the overall performance of the battery. While increasing the nickel content in ternary materials effectively improves battery capacity, it also introduces a series of problems. For example, high-nickel materials have poor stability in air, readily reacting with moisture and carbon dioxide to form residual lithium compounds on the surface, thus reducing electrochemical performance. Furthermore, during battery cycling, nickel ions are prone to valence state changes, leading to mixing with lithium ions and altering the material structure, which adversely affects cycle stability and rate performance.

[0003] To address the aforementioned issues, high-nickel single-crystal cathode materials have attracted widespread attention. These materials are grown from single particles, resulting in a complete and uniform structure that facilitates lithium-ion migration and diffusion and reduces side reactions with the electrolyte. However, their large specific surface area exacerbates side reactions at the electrode-electrolyte interface, leading to a decrease in coulombic efficiency. Furthermore, due to the similar radii of lithium and nickel ions, cation mixing easily occurs during charge and discharge, further inducing structural transformation and the formation of irreversible phases.

[0004] Elemental doping is considered one of the effective methods to improve the performance of cathode materials. Appropriate doping can enhance the structural stability of high-nickel ternary materials, suppress lithium-nickel mixing, rock salt phase formation, and oxygen loss, thereby improving the reversibility of the electrode reaction. However, doping also has problems such as introducing impurities and reducing capacity; therefore, the rational selection of the type and amount of doping elements is particularly crucial. Previous studies have shown that introducing niobium ions (Nb) can... 5+ Niobium doping can enhance the structural stability and improve conductivity of materials; however, the electrochemical performance of niobium-doped materials at high temperatures is still not ideal.

[0005] In terms of material preparation, traditional high-temperature solid-state sintering processes often employ conventional heating or two-stage sintering methods, which make it difficult to precisely control crystal nucleation and grain growth, easily leading to uneven grain size and exacerbated cation mixing. Although two-stage sintering has improved this to some extent, it still has shortcomings in promoting uniform diffusion of dopants, improving lattice construction, and releasing internal stress in materials, resulting in limited structural stability of the prepared materials, especially significant degradation in cycling performance under high temperature and high rate conditions.

[0006] Patent application CN119905562A discloses a modified high-nickel ternary cathode material, its preparation method, and its application. The method includes the following steps: mixing a high-nickel ternary cathode material containing doped elements, bismuth tungstate, and alumina, followed by sintering to obtain the modified high-nickel ternary cathode material. The doped elements include at least one selected from titanium, yttrium, tungsten, and niobium. The sintering temperature is 400-800℃. Batteries made from the modified high-nickel ternary cathode material prepared by this method exhibit good cycle stability and thermal stability. While this method can improve the poor cycle stability and thermal stability of high-nickel ternary materials, the entire process is complex and could lead to resource waste in actual industrial production.

[0007] In view of the problems of complex process, poor structural stability, and poor high-temperature performance and cycle performance caused by improper selection of dopants in the current preparation process of single crystal ternary cathode materials, there is an urgent need to develop a simple preparation method for single crystal ternary cathode materials with better structural stability and cycle performance. Summary of the Invention

[0008] The purpose of this invention is to provide a niobium-yttrium co-doped single-crystal ternary cathode material, its preparation method, and its application, so as to solve the technical problems of complex process, poor structural stability, and poor cycle performance in the preparation process of single-crystal ternary cathode materials.

[0009] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material, comprising the following steps: Step 1: Ball mill and mix the ternary precursor, lithium source, additives Nb2O5 and Y2O3; Step 2: Under an oxygen atmosphere, the mixed materials are sintered in three stages at high temperatures. First stage: Increase the temperature from room temperature to 450-550℃ at a heating rate of 3-5℃ / min, and hold at that temperature for 1-2 hours; Second stage: Increase the temperature to 750-850℃ at a heating rate of 2-3℃ / min and hold for 4-6 hours; The third stage: raise the temperature to 930-950℃ at a heating rate of 2-3℃ / min and hold for 10-14 hours; Step 3: After sintering, the niobium-yttrium co-doped single-crystal ternary cathode material is obtained by sieving.

[0010] In some possible implementations, the lithium source is one of lithium carbonate, lithium hydroxide monohydrate, and lithium nitrate.

[0011] In some possible implementations, the ternary precursor is Ni. 0.6 Co 0.1 Mn0.3 (OH)2, Ni 0.65 Co 0.15 Mn 0.20 (OH)2 and Ni 0.6 Co 0.2 Mn 0.2 One of (OH)2.

[0012] In some possible implementations, the molar ratio of lithium in the lithium source to the sum of Ni, Co, and Mn in the ternary precursor is 1.04-1.045:1.

[0013] In some possible implementations, Nb2O5 accounts for 800-1000 ppm of the total mass of Nb2O5, lithium source and ternary precursor; Y2O3 accounts for 500-800 ppm of the total mass of Y2O3, lithium source and ternary precursor.

[0014] In some possible implementations, the temperature is first increased to 500℃ at 3℃ / min and sintered at a constant temperature for 1 hour; then increased to 750℃ at 3℃ / min and sintered at a constant temperature for 5 hours; finally increased to 945℃ at 2℃ / min and sintered at a constant temperature for 12 hours. The sieving process uses a 325-mesh sieve.

[0015] The second aspect of this invention provides a niobium-yttrium co-doped single-crystal ternary cathode material, which is prepared by the above-described preparation method.

[0016] In some possible implementations, the median particle size of niobium-yttrium co-doped single-crystal ternary cathode materials is 4-5 μm.

[0017] The third aspect of this invention provides the application of a niobium-yttrium co-doped single-crystal ternary cathode material in lithium batteries.

[0018] The beneficial effects of this invention are: While ensuring the room-temperature electrochemical performance of the cathode material, this invention improves the high-temperature electrochemical performance and structural stability of the cathode material by employing a three-stage high-temperature sintering method to modify the ternary precursor with niobium and yttrium co-doping. By precisely controlling the heating stage and holding time of the sintering process, uniform grain growth and efficient solid solution of dopant elements are achieved.

[0019] This invention employs a three-stage high-temperature sintering method to prepare single-crystal ternary cathode materials. This method achieves uniform grain size, dense structure, and complete solid solution of dopant elements through staged low-temperature impurity removal, medium-temperature crystallization, and high-temperature crystallization growth, effectively improving the structural stability and electrochemical consistency of the material. Compared with conventional sintering or two-stage sintering, the three-stage sintering process of this invention effectively avoids problems such as localized overheating, lattice defects, or compositional segregation caused by excessively rapid heating. The process offers greater controllability, and the prepared material exhibits superior performance in high-temperature cycling and rate capability, making it more suitable for large-scale industrial production.

[0020] This invention reduces the degree of cation mixing and increases the inter-crystal spacing by co-doping with niobium and yttrium, which is beneficial for the intercalation and deintercalation of lithium ions between layers, thereby improving electrochemical performance. The single-crystal ternary cathode material prepared by this invention has good structural stability and safety. It can effectively suppress phase transition and structural damage during charging and discharging, reduce the risk of thermal runaway, and meet the high safety requirements of lithium batteries in fields such as electric vehicles and energy storage systems. Attached Figure Description

[0021] The invention will now be further described with reference to the accompanying drawings.

[0022] Figure 1 This is a schematic diagram of the process flow for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to Embodiment 1 of the present invention. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] The following is a detailed description of a niobium-yttrium co-doped single-crystal ternary cathode material, its preparation method, and its application, based on embodiments of this application.

[0025] Example 1 This embodiment provides a niobium and yttrium co-doped single-crystal ternary cathode material based on a three-stage high-temperature sintering method. A schematic diagram of the process flow is shown below. Figure 1 As shown. Specifically, it includes the following steps: Step 1: Mixing: Mix the ternary precursor Ni 0.6 Co 0.1 Mn 0.3(OH)2, Li2CO3, additives Nb2O5 and Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt and manganese was 1.042, the additive Nb2O5 accounted for 800 ppm of the total mass of Nb2O5, lithium source and ternary precursor; and Y2O3 accounted for 650 ppm of the total mass of Y2O3, lithium source and ternary precursor.

[0026] Step 2, Filling the sagger: After filling the mixed materials into the sagger, shake well and mark the grid lines.

[0027] Step 3, Sintering: Place the sagger into a muffle furnace and perform three-stage high-temperature sintering in an oxygen atmosphere: First stage: Increase the temperature to 500℃ at a rate of 3℃ / min and hold for 1 hour; Second stage: Increase the temperature to 750℃ at 3℃ / min and hold for 5 hours; Third stage: Increase the temperature to 945℃ at a rate of 2℃ / min and hold for 12 hours.

[0028] Step 4: Crushing and sieving: The sintered material in the crucible is crushed using a universal crusher and then sieved using a 325-mesh sieve to obtain niobium and yttrium co-doped single-crystal ternary cathode material.

[0029] Example 2 The difference between this embodiment and Embodiment 1 lies in the temperature of the third stage in step three. Specifically, in step three, sintering: the sagger is placed in a muffle furnace and subjected to three-stage high-temperature sintering in an oxygen atmosphere. First stage: Increase the temperature to 500℃ at a rate of 3℃ / min and hold for 1 hour; Second stage: Increase the temperature to 750℃ at 3℃ / min and hold for 5 hours; Third stage: Increase the temperature to 930℃ at a rate of 2℃ / min and hold for 14 hours.

[0030] The remaining raw materials and preparation process are the same as in Example 1.

[0031] Example 3 The difference between this embodiment and Embodiment 1 lies in the holding time in the third stage of step three. Specifically, in step three, sintering: the sagger is placed in a muffle furnace and subjected to three-stage high-temperature sintering in an oxygen atmosphere. First stage: Increase the temperature to 500℃ at a rate of 3℃ / min and hold for 1 hour; Second stage: Increase the temperature to 750℃ at 3℃ / min and hold for 5 hours; Third stage: Increase the temperature to 950℃ at a rate of 2℃ / min and hold for 10 hours.

[0032] The remaining raw materials and preparation process are the same as in Example 1.

[0033] Example 4 The difference between this embodiment and Example 1 lies in the proportion of additives added. Specifically, step one, mixing: the ternary precursor Ni... 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, additives Nb2O5 and Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt and manganese was 1.042, the additive Nb2O5 accounted for 1000 ppm of the total mass of Nb2O5, lithium source and ternary precursor; and Y2O3 accounted for 650 ppm of the total mass of Y2O3, lithium source and ternary precursor.

[0034] The remaining raw materials and preparation process are the same as in Example 1.

[0035] Example 5 The difference between this embodiment and Embodiment 1 is that, in step one, mixing: the ternary precursor Ni... 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, additives Nb2O5 and Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt and manganese was 1.042, and the additive Nb2O5 accounted for 800 ppm of the total mass of Nb2O5, lithium source and ternary precursor; Y2O3 accounted for 800 ppm of the total mass of Y2O3, lithium source and ternary precursor.

[0036] The remaining raw materials and preparation process are the same as in Example 1.

[0037] Comparative Example 1 This comparative example provides a niobium-doped single-crystal ternary cathode material. The sintering process used in its fabrication is the same three-stage high-temperature sintering method as in Example 1, but without the addition of Y₂O₃. Specifically, it includes the following steps: Step 1: Mixing: Mix the ternary precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, and additive Nb2O5 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt, and manganese was 1.042, and the additive Nb2O5 accounted for 800 ppm of the total mass of Nb2O5, lithium source, and ternary precursor.

[0038] Step 2, Filling the sagger: After filling the mixed materials into the sagger, shake well and mark the grid lines.

[0039] Step 3, Sintering: The same three-stage high-temperature sintering procedure as in Example 1 is adopted.

[0040] Step 4: Crushing and sieving: The sintered material in the crucible is crushed using a universal crusher and then sieved using a 325-mesh sieve to obtain niobium-doped single-crystal ternary cathode material.

[0041] Comparative Example 2 This comparative example provides a yttrium-doped single-crystal ternary cathode material. The sintering process used in its fabrication is the same three-stage high-temperature sintering method as in Example 1, but without the addition of Nb₂O₅. Specifically, it includes the following steps: Step 1: Mixing: Mix the ternary precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, and additive Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt, and manganese was 1.042, and the additive Y2O3 accounted for 650 ppm of the total mass of Y2O3, lithium source, and ternary precursor.

[0042] Step 2, Filling the sagger: After filling the mixed materials into the sagger, shake well and mark the grid lines.

[0043] Step 3, Sintering: The same three-stage high-temperature sintering procedure as in Example 1 is adopted.

[0044] Step 4: Crushing and sieving: The sintered material in the crucible is crushed using a universal crusher and then sieved using a 325-mesh sieve to obtain yttrium-doped single-crystal ternary cathode material.

[0045] Comparative Example 3 This comparative example provides a niobium and yttrium co-doped single-crystal ternary cathode material. The difference in its fabrication process from Example 1 lies only in the use of a conventional one-step sintering method. Specifically, it includes the following steps: Step 1: Mixing: Mix the ternary precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, Nb2O5, and Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt, and manganese was 1.042. The additive Nb2O5 accounted for 800 ppm of the total mass of Nb2O5, lithium source, and ternary precursor; and Y2O3 accounted for 650 ppm of the total mass of Y2O3, lithium source, and ternary precursor.

[0046] Step 2, Filling the sagger: After filling the mixed materials into the sagger, shake well and mark the grid lines.

[0047] Step 3, sintering: Place the sagger into a muffle furnace and heat it directly from room temperature to 945℃ at a rate of 3℃ / min under an oxygen atmosphere, and hold it at that temperature for 12 hours.

[0048] Step 4: Crushing and sieving: The sintered material in the crucible is crushed using a universal crusher and then sieved using a 325-mesh sieve to obtain niobium and yttrium co-doped single-crystal ternary cathode material.

[0049] Comparative Example 4 This comparative example provides a niobium and yttrium co-doped single-crystal ternary cathode material. The difference in its fabrication process from Example 1 lies only in the use of a two-stage sintering method. Specifically, it includes the following steps: Step 1: Mixing: Mix the ternary precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3, Nb2O5, and Y2O3 were placed in an all-around planetary ball mill and mixed at 260 rpm / min for 3 hours to obtain a mixed material. In the mixed material, the molar ratio of lithium to nickel, cobalt, and manganese was 1.042. The additive Nb2O5 accounted for 800 ppm of the total mass of Nb2O5, lithium source, and ternary precursor; and Y2O3 accounted for 650 ppm of the total mass of Y2O3, lithium source, and ternary precursor.

[0050] Step 2, Filling the sagger: After filling the mixed materials into the sagger, shake well and mark the grid lines.

[0051] Step 3, sintering: Place the sagger into a muffle furnace and, under an oxygen atmosphere, first heat to 600℃ at 3℃ / min and sinter at a constant temperature for 2 hours; then heat to 945℃ at 2.5℃ / min and sinter at a constant temperature for 12 hours.

[0052] Step 4: Crushing and sieving: The sintered material in the crucible is crushed using a universal crusher and then sieved using a 325-mesh sieve to obtain niobium and yttrium co-doped single-crystal ternary cathode material.

[0053] Test case Using the single-crystal ternary cathode material prepared in the examples and comparative examples as the cathode active material, the cathode active material: conductive agent (SP): binder (PCDF) = 95:5:5 by mass to make a cathode slurry, which is then coated on the cathode current collector to form the cathode. The lithium sheet is used as the anode. A conventional rate-type electrolyte is selected. The above cathode sheet, separator, anode lithium metal sheet, electrolyte, etc. are assembled into a button battery in a glove box filled with argon gas and the electrochemical performance of the battery is tested. The test results are shown in Tables 1-5 below.

[0054] The rate performance of the samples prepared in Example 1 and Comparative Examples 1-4 at 45℃ was tested after one cycle of charge-discharge at 3.0-4.45V, 0.1C, 0.5C, 1C, and 3C. The results are shown in Table 1 below: Table 1

[0055] The test results of the samples prepared in Example 1 and Comparative Examples 1-4 at 45℃ after 50 cycles at 3.0-4.5V and 1C are shown in Table 2 below: Table 2

[0056] The samples prepared in Examples 1-5 and Comparative Examples 1-2 at 25℃ were subjected to charge-discharge rate performance tests after one cycle at 3.0-4.45V, 0.1C, 0.5C, 1C, and 3C. The results are shown in Table 3 below: Table 3

[0057] The test results of the samples prepared in Examples 1-5 and Comparative Examples 1-2 at 25°C for 50 cycles at 3.0-4.5V and 1C are shown in Table 4 below: Table 4

[0058] Table 1 shows the rate performance test results of different samples at 45℃ after one cycle of charge-discharge at 3.0-4.45V, 0.1C, 0.5C, 1C, and 3C. During the lithium-ion insertion-extraction reaction, increased current led to polarization, resulting in a decrease in the discharge capacity of the samples. With increasing charge-discharge rate, the capacity of the niobium-doped single-crystal ternary cathode material at 3C was 142.7 mAh / g, while the capacity of the yttrium-doped single-crystal ternary cathode material at 3C was 140.1 mAh / g. The rate performance of the niobium and yttrium co-doped single-crystal ternary cathode material was higher than that of the niobium-doped and yttrium-doped single-crystal ternary cathode materials alone. The discharge specific capacity of the niobium and yttrium-doped single-crystal ternary cathode material at 3C reached 148.2 mAh / g, indicating that niobium and yttrium co-doping can improve the rate performance and capacity of the material at high temperatures.

[0059] Table 2 shows the test results of different samples at 45℃ after 50 cycles at 3.0-4.5V and 1C rate. The discharge capacities of the niobium-yttrium co-doped single-crystal ternary cathode material, the niobium-doped single-crystal ternary cathode material, and the yttrium-doped single-crystal ternary cathode material after 50 cycles were 103.5 mAh / g, 92.1 mAh / g, and 93.6 mAh / g, respectively, with corresponding capacity retention rates of 56.5%, 50.8%, and 51.3%. The results indicate that the niobium-yttrium co-doped single-crystal ternary cathode material exhibits the best cycling performance. After 50 cycles, its discharge specific capacity is 11.4 mAh / g higher than that of the niobium-doped and yttrium-doped single-crystal ternary cathode materials, respectively, and its cycle retention rates are 5.7 and 5.2 percentage points higher, respectively. This suggests that niobium-yttrium co-doping can improve the cycling performance of the material at high temperatures. The three-stage sintering method in this invention, through an optimized heating program, better promotes the crystallization and element homogenization of the material, thereby playing a key role in improving capacity and maintaining cycle stability.

[0060] Table 3 shows the rate performance test results of different samples at 25℃ after one cycle of charge-discharge at 3.0-4.45V, 0.1C, 0.5C, 1C, and 3C. The niobium-doped single-crystal ternary cathode material has a capacity of 146.8 mAh / g at 3C, the yttrium-doped single-crystal ternary cathode material has a capacity of 143.5 mAh / g at 3C, while the discharge specific capacity of the niobium and yttrium co-doped single-crystal ternary cathode material can reach 150.2 mAh / g at 3C. This indicates that co-doping with niobium and yttrium can improve the rate performance and capacity of the material at room temperature.

[0061] Table 4 shows the test results of different samples at 25℃ after 50 cycles at 3.0-4.5V and 1C rate. The niobium-doped single-crystal ternary cathode material exhibited a discharge specific capacity of 141.3 mAh / g and a capacity retention of 83.7% after 50 cycles. The yttrium-doped single-crystal ternary cathode material exhibited a discharge specific capacity of 140.8 mAh / g and a capacity retention of 84.8% after 50 cycles. The niobium and yttrium co-doped single-crystal ternary cathode material showed the highest discharge specific capacity after 50 cycles, reaching 150.4 mAh / g, with a capacity retention of 86.8%, which is 3.1 and 2 percentage points higher than the niobium-doped and yttrium-doped single-crystal ternary cathode materials, respectively. This indicates that simultaneous doping with both yttrium and niobium can improve the cycling performance of the material at room temperature.

[0062] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0063] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material, characterized in that, Includes the following steps: Step 1: Ball mill and mix the ternary precursor, lithium source, and additives; the additives include Nb2O5 and Y2O3; Step 2: Under an oxygen atmosphere, the mixed materials are sintered in three stages at high temperatures. First stage: Increase the temperature from room temperature to 450-550℃ at a heating rate of 3-5℃ / min, and hold at that temperature for 1-2 hours; Second stage: Increase the temperature to 750-850℃ at a heating rate of 2-3℃ / min and hold for 4-6 hours; The third stage: raise the temperature to 930-950℃ at a heating rate of 2-3℃ / min and hold for 10-14 hours; Step 3: After sintering, the niobium-yttrium co-doped single-crystal ternary cathode material is obtained by sieving.

2. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, The lithium source is one of lithium carbonate, lithium hydroxide monohydrate, and lithium nitrate.

3. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, The ternary precursor is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Ni 0.65 Co 0.15 Mn 0.20 (OH)2 and Ni 0.6 Co 0.2 Mn 0.2 One of (OH)2.

4. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, The molar ratio of lithium in the lithium source to the sum of Ni, Co, and Mn in the ternary precursor is 1.04-1.

045.

5. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, Nb2O5 accounts for 800-1000 ppm of the total mass of Nb2O5, lithium source and ternary precursor.

6. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, Y2O3 accounts for 500-800 ppm of the total mass of Y2O3, lithium source and ternary precursor.

7. The method for preparing a niobium-yttrium co-doped single-crystal ternary cathode material according to claim 1, characterized in that, First, the temperature is increased to 500℃ at 3℃ / min and sintered at a constant temperature for 1 hour; then, the temperature is increased to 750℃ at 3℃ / min and sintered at a constant temperature for 5 hours; finally, the temperature is increased to 945℃ at 2℃ / min and sintered at a constant temperature for 12 hours.

8. A niobium-yttrium co-doped single-crystal ternary cathode material, characterized in that, Prepared by the preparation method according to any one of claims 1-7.

9. The niobium-yttrium co-doped single-crystal ternary cathode material according to claim 8, characterized in that, The median particle size of niobium-yttrium co-doped single-crystal ternary cathode material is 4-5 μm.

10. The application of the niobium-yttrium co-doped single-crystal ternary cathode material as described in claim 8 in lithium batteries.

Citation Information

Patent Citations

  • Modified high-nickel ternary positive electrode material as well as preparation method and application thereof

    CN119905562A